1996
DOI: 10.1557/jmr.1996.0140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering periods on the microstructure and electrical transport properties of high-Tc superconducting Bi–(Pb)–Sr–Ca–Cu–O tapes

Abstract: The effect of sintering periods for monocore (Bi, Pb)2Sr2Ca2Cu3O10+x (Bi-2223) tapes on microstructure and critical current density (Jc) have been studied. The results show that long sintering periods (of duration ≥100 h) give better grain growth, but greater misalignment. Prolonged sintering also necessitates the increase in porosity of the core due to random grain growth, increasing the chance of penetrating into the silver matrix and oxide core interface. Critical currents for long sintering periods are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In summary, both SEM and XRD measurements clearly indicate that 40 h after the first annealing the Bi(2223) platelets are already present in their final morphology and orientation and that no decomposition of the Bi(2223) occurs up to 240 h. In addition, we found no evidence of an increase in the ceramic core porosity, as reported by some authors (e.g. [23]).…”
Section: Microstructuresupporting
confidence: 84%
“…In summary, both SEM and XRD measurements clearly indicate that 40 h after the first annealing the Bi(2223) platelets are already present in their final morphology and orientation and that no decomposition of the Bi(2223) occurs up to 240 h. In addition, we found no evidence of an increase in the ceramic core porosity, as reported by some authors (e.g. [23]).…”
Section: Microstructuresupporting
confidence: 84%
“…Considerable progress has been made in fabricating (Bi, Pb) 2 Sr 2 Ca 2 Cu 3 O x (Bi-2223) tapes or wires with high critical current densities that are attractive for electric power and high-field magnet applications [1][2][3][4][5][6][7][8][9]. The transport critical current density of the Bi-2223 tapes has been found to depend significantly on heat treatment temperature [4], precursor powder [6,9,10], sintering time [11] and mechanical deformation [9,12]. Although some parameters are believed to be optimized, it should be emphasized that a better control of the variables, for example, the precursor powder, is still needed in order to increase the reproducibility of the transport properties in long tapes.…”
Section: Introductionmentioning
confidence: 99%
“…3), which agrees with earlier reports. 19 We found that grains grow in the a/b plane from a size of ϳ15 m at 0.3 h to ϳ80 m at 50 h, whereas grain growth in the c-direction is negligible. Although the amount of liquid probably is insufficient for particle rearrangement beyond 4 h, the residual liquid could be sufficient to enhance grain growth.…”
Section: Resultsmentioning
confidence: 60%